2021
DOI: 10.1002/ajh.26098
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid and lymphoid vacuolation in VEXAS syndrome

Abstract: A 70-year-old Chinese male presented with unexplained fever, relapsing polychondritis, macrocytic anemia, acute necrotising lymphadenitis, skin papules that were in keeping histologically with Kikuchi-Fujimoto disease, and pulmonary embolism secondary to extensive unprovoked right lower limb deep vein thrombosis. Given the recent discovery of VEXAS (vacuoles, E1 enzyme, X-linked,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…The most commonly reported cutaneous manifestations of VEXAS syndrome are neutrophilic dermatosis and leukocytoclastic vasculitis. 18 Additional manifestations including septal panniculitis or erythema nodosum, 2,9,19,20 injection site reactions to Interleukin-1 receptor antagonists, 2,3,8,21,22 Kikuchi-Fujimoto disease 23,24 livedo racemosa, 13 lupus tumidus-like eruption, 25 polyarteritis nodosa, 13,26 and systemic lupus erythematosus, 27,28 have been encountered in multiple cases. Other manifestations including idiopathic cholesterol embolization syndrome, 29 erythema multiforme, 19 urticarial vasculitis, 22 and digital necrosis secondary to type III cryoglobulinemia 7 appear in isolated case reports.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly reported cutaneous manifestations of VEXAS syndrome are neutrophilic dermatosis and leukocytoclastic vasculitis. 18 Additional manifestations including septal panniculitis or erythema nodosum, 2,9,19,20 injection site reactions to Interleukin-1 receptor antagonists, 2,3,8,21,22 Kikuchi-Fujimoto disease 23,24 livedo racemosa, 13 lupus tumidus-like eruption, 25 polyarteritis nodosa, 13,26 and systemic lupus erythematosus, 27,28 have been encountered in multiple cases. Other manifestations including idiopathic cholesterol embolization syndrome, 29 erythema multiforme, 19 urticarial vasculitis, 22 and digital necrosis secondary to type III cryoglobulinemia 7 appear in isolated case reports.…”
Section: Discussionmentioning
confidence: 99%
“…One patient also had weakly positive IgM anticardiolipin antibodies. Other tests for thrombophilia included paroxysmal nocturnal haemoglobinuria, antithrombin III activity, and protein C or S activity were unremarkable [2]. Although Beck et al reported that UBA1 gene mutations were identified only in males, where males have a higher risk of first and recurrent venous thrombosis than women, 3 studies have reported the development of VEXAS syndrome in 8 females [3,10,11].…”
Section: Discussionmentioning
confidence: 99%
“…VEXAS (Vacuoles, E1 enzyme, X-linked, autoinflammatory, somatic) syndrome [1] is described as a late-onset autoinflammatory syndrome exhibiting a spectrum of systemic inflammatory manifestations as well as significant haematologic abnormalities such as macrocytic anaemia, marrow dysplasia, vacuolisation in myeloid cells [2] and thrombosis. Several published case series [1,[3][4][5][6][7][8][9][10] have observed a high prevalence of venous thromboembolism (VTE) in patients with VEXAS syndrome of between 10% and 56%, with a significant mortality rate (27%-50%).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a medical history that may cause copper deficiency, such as total parenteral hyperalimentation, is suggestive to diagnosis. In contrast, in VEXAS syndrome, numerous round vacuoles consisting of lipid droplets and disordered cellular organelles occur in myeloid and erythroid precursors [1,2,14].…”
Section: Open Accessmentioning
confidence: 92%